Interactive Read Aloud as An Effort to Improve Foreign Language Skills at Early Age - Elwin Walimatul Fara; Rohinah Rohinah; Na'imah Na'imah (AL-ISHLAH: Jurnal Pendidikan, 2023)
One of the efforts of developing foreign language skills in early childhood is listening skills. Various kinds of listening activities that can be applied to early childhood are packed with interesting and fun activities. One of the methods for listening to non-stop that invites children to actively participate is the interactive read aloud method. The purpose of this study is to review  interactive read aloud method as an effort to improve foreign language skills in early childhood. The results of the discussion showed that foreign language learning with the interactive read aloud method is effective and can invite children to actively participate, understand the text, and be able to retell the story that is being played